Insight into the relationship between entrepreneurship orientations and performance: The case of SME exporters in Malaysia - Ismail, Md Daud; Md. Isa, Azwardi; Ali, Mohd Helmi (Universiti Kebangsaan Malaysia, 2013)
The rise in the number of small and medium businesses competing in foreign markets has led to growing interest among researchers in the study of the international activities of these firms. Previous studies have focused on how small businesses successfully compete in the market alongside larger and resourceful firms despite the former’s scarcity of resources.In this light, we develop the conceptual framework that is based upon the resource-based view, and explore the link between firm-specific resources and export performance.This study examines the relationships between entrepreneurial dimensions, namely pro-activeness, risk-taking, and innovativeness, and the performance of the exporter.Based on a sample of 220 SMEs, this study found that pro-activeness affects export performance positively and significantly.In addition, innovativeness was found to be significantly associated with export performance.Finally, the paper ends with the conclusion, a presentation of the limitations of the study, and suggestions for future research.